AIEgens with bright mechanoluminescence and thermally activated delayed fluorescence derived from (9H-carbazol-9-yl)(phenyl)methanone. (March 2020) - Liu, Cong; Chen, Jiehuan; Xu, Chao; Hao, Hongmin; Xu, Bingjia; Hu, Dehua; Shi, Guang; Chi, Zhenguo
Abstract: Two compounds derived from (9 H -carbazol-9-yl)(phenyl)methanone (TPhBCz and TPh2BCz) showing characteristics of AIE and TADF were synthesized and investigated. Small energy gap (Δ E ST ) between S1 and T1 may account for the TADF properties of the compounds. Moreover, TPhBCz showed strong mechanoluminescence (ML) without any pretreatment, while there was no ML for the TPh2BCz substituted with two bromine groups. The careful investigation on the data of single crystal structures and theoretical calculations demonstrated that the compact molecular packing as well as abundant and intense intermolecular interactions of the crystal lead to the prominent ML performance of TPhBCz. These results help to understand the unique ML process and provide a design and synthetic strategy for new materials exhibited AIE, TADF, and ML simultaneously. Graphical abstract: An aggregation-induced emission compound shows efficient thermally activated delayed fluorescence and bright mechanoluminescence. Image 1 Highlights: AIE compounds substituted with bromine group(s) have been designed and synthesized. TPhBCz with efficient TADF and bright ML. Small Δ E ST values account for the TADF properties. Compact molecular packing and intense intermolecular interactions lead to the efficient ML.